Implementasi Metode Token Economy untuk Meningkatkan Kedisiplinan Anak Usia Dini Kelas A di RA Ta Kottah Daleman Galis Bangkalan - Alfiya, Luluk (WALADI, 2024)
The background of this research is that educators find it difficult to find a way to encourage students in the teaching process, therefore educators have the initiative to develop children's learning with the token economy method so that children are more enthusiastic in learning because early childhood with prizes makes learning more intense. This research was conducted at RA Ta Kottah Daleman Galis Bangkalan and the type of research used qualitative research. The data collection method uses interview, observation, and documentation methods. The subjects of the study were educators and students at RA Ta Kottah in Daleman Village, Galis district, Bangkalan district. From the results of the discussions and research that has been carried out, the research has obtained a consensus that the early childhood learning process must be carried out creatively and funnily so that students can be more enthusiastic about the learning provided by educators. Meanwhile, the result of the analysis of data on early childhood discipline using the token economy method at RA Ta Kottah in Daleman Galis Bangakalan village is that there are benefits of discipline by using the token economy, it can make it easier for educators to create new ideas obtained through the token economy so that it can make it easier to improve children's discipline